ANALISIS SWOT UNTUK MENENTUKAN STRATEGI KOMPETITIF PADA HADI SUKIRNO LEATHER WORK & HANDICRAFT - Nurwantoro Nurwantoro; Wawan Budi Setyawan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2015)
With increasing global competition, the company is required to always pay attention to the market and compete situation more competitive in determining strategy. Competitive strategy is one way to determine the competitiveness of each strength. Use of an effective SWOT analysis can play an important role in determining the competitive strategy, in order to know the strengths, weaknesses, opportunities and threats faced by enterprise IT in maintaining the viability and continuity of the company. A problem in which you want to find the answer in this study is "" whether SWOT strategy analysis is appropriate in order to improve production on Integration and how competitive strategy applied by the company in addressing global competition.? "". In connection with the proposed hypothesis problem as follows: "" allegedly using SWOT analysis to increase sales so the company experienced profits (surplus) "". This study uses primary data by giving questionnaires and secondary data to acquire archives or documents Along with the problem and research hypothesis, the research is done by using analytical methods IFAs to analyze the internal factors, the analysis of EFAS to external factors, then, included into the model kuantitif ie SWOT matrix. Results of the analysis showed that, by using analysis of IFAS and EFAS and using SWOT analysis shows the company's position in the cell 2, the strategy chosen to support the attainment of the objectives of the company are "" strategy ST ""